Cross-Sectional Assessment of the Roles of Comorbidities in Resting and Activity-Related Dyspnea in Severely Obese Women. (August 2013) - Essalhi, Mohamed; Gillaizeau, Florence; Chevallier, Jean-Marc; Ducloux, Roxane; Chevalier-Bidaud, Brigitte; Callens, Etienne; Graba, Semia; Gillet-Juvin, Karine; Altman, Jean-Jacques; Louis, Bruno; Mahut, Bruno; Delclaux, Christophe
Abstract : Objectives. Obesity has been associated with a lesser degree of asthma control that may be biased by other comorbidities. The objectives of this cross-sectional study were to describe resting and activity-related dyspnea complaints according to the presence of obesity-related comorbidities (asymptomatic airway hyperresponsiveness (AHR), asthma, gastroesophageal reflux disease (GERD) and sleep-disordered breathing (SDB)). We hypothesized that obese women can exhibit both resting and activity-related dyspnea, independently of the presence of asthma. Methods. Severely obese (body mass index (BMI) > 35 kg m −2 ) women prospectively underwent description of resting and activity-related dyspnea (verbal descriptors and Medical Research Council (MRC) scale), pulmonary function testing (spirometry, absolute lung volumes, and methacholine challenge test), oesogastro-duodenal fibroscopy, and overnight polygraphy. Thirty healthy lean women without airway hyperresponsiveness were enrolled. Results. Resting dyspnea complaints were significantly more prevalent in obesity (prevalence 41%) than in healthy lean women (prevalence 3%). Chest tightness and the need for deep inspirations were independently associated with both asthma and GERD while wheezing and cough were related to asthma only in obese women. Activity-related dyspnea was very prevalent (MRC score > 1, 75%), associated with obesity, with the exception of wheezing on exertion due to asthma. Asymptomatic AHR and SDB did not affect dyspneic complaints. Conclusions. In severely obese women referred for bariatric surgery, resting dyspnea complaints are observed in association with asthma or GERD, while activity-related dyspnea was mainly related to obesity only. Consequently, asthma does not explain all respiratory complaints of obese women.